Comparison of the application of intra-articular and intravenous tranexamic acid to reduce blood loss during primary total knee arthroplasty - Genc, Ahmet Serhat; Arar, Korkut; Agar, Anil; Guzel, Nizamettin (Sindicato Secretarias Estado Sao Paulo, 2023)
Tranexamic acid (TXA) is frequently administered intravenously because it is recognized as a safe and effective procedure. This study's objective is to evaluate the effectiveness of intravenous and intra-articular TXA treatments in patients who have had primary unilateral knee joint replacement. Patients were divided into groups based on TXA applications. Group A patients, those who received intravenous TXA, Group B patients, those who received intraarticular TXA, and Group C patients were intended to serve as the control group. Age, gender, ASA scores, length of hospital stay, preoperative, postoperative, and discharge hemoglobin and hematocrit levels, and the quantity of blood product transfusion given to thepatients was analyzed retrospectively. Analysis of the patient's postoperative Hb values revealed that group C patients had lower Hb values (p < 0.05). Postoperative Hct levels were also seen to be significantly lower in group C individuals (p < 0.05). When the patients' Hb levels were measured at discharge, it was discovered that group C patients had lower Hb levels (p < 0.05). The Hct values of group C patients at discharge were also found to be considerably lower (p < 0.05). It was found that group C patients received significantly more blood transfusions than the other groups (p < 0.05) when the number of patient blood transfusions was compared between the groups. Intravenous and intra-articular TXA successfully minimize blood loss in primary TKA. The benefits of intra-articular administration over intravenous administration include convenience of administration, local application, and a higher level of safety.
Keywords: Tranexamic Acid; Blood Loss; Total Knee Arthroplasty